Investigation of TPP-Chitosomes particles structure and stability as encapsulating agent of cholecalciferol - Iida,Aline Sayuri Lima (2019)
Abstract Tripolyphosphate (TPP)-chitosomes were produced aiming at the encapsulation and conservation of vitamin D3. This hybrid system is made of liposomes, vesicles consisting of phospholipid bilayers, surrounded by chitosan wall ionic-crosslinked with TPP. Chitosan concentrations (2 and 4 mg mL-1) were tested and the vitamin stability in aqueous dispersions monitored for 49 days. The results confim that D3 remained stable throughout the analyzed period (49 days), whereas the non-encapsulated vitamin totally degrades after the second week of storage. The particle diameters ranged from 0.1 to 5 μm with good colloidal stability (+22 to +48 mV), and encapsulation efficiency of 97%. Thermal stability was also improved when using the TPP-chitosomes. The protection performed was attributed to the stable interactions conferred by the phospholipids crosslinking with the chitosan amino groups and a formation of a net of hydrogen bonds established amongst the hydroxyl groups of the interacting compounds as revealed by infrared spectroscopy.